Prisoner and Goods Control System Design Evidence Using MVC and UAT Models at the Provincial National Narcotics Agency - Okkita Rizan; Hamidah Hamidah; Delpiah Wahyuningsih; Sarwindah Sarwindah (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2022)
In Indonesia, there is a special agency tasked with dealing with the misuse of prohibited goods, namely the National Narcotics Agency, abbreviated as BNN. Apart from being at the center, BNN is also at the provincial level. At the National Narcotics Agency, there is a section or section that has a special function to manage the supervision of prisoners and evidence in the form of narcotics. The problem is, the administrative process is still irregular, archives are difficult to find, and several other important things, which are certainly very influential for the next process and follow-up. This study aims to help design a system that can manage the process of monitoring prisoners and evidence. For the research method, the author uses a prototype model, Model View Controller (MVC), and User Acceptance Test (UAT). The results showed that the system can work well in assisting the process of monitoring prisoners and evidence with a percentage of 54.29% strongly agree and 64.00% agree with the developed system model.